Дослідження впливу природи електродного матеріалу на параметри електросинтезу водню - Байрачний, Борис Іванович; Желавська, Юлія Анатоліївна; Вороніна, Олена Володимирівна; Ковальова, Ганна Андріївна; Руденко, Наталія Олександрівна (НТУ "ХПІ", 2016)
Досліджена поведінка електродних матеріалів при електросинтезі водню в 3% розчині хлорида амонія. Доведено можливість використання ВТ6 сплаву як катодного матеріалу.в практичному електролізі в широкому інтервалі густин струму та рН із-за його високої хімічної стійкості. Використання анодів зі сталі 12Х1МФ не є ефективним. Електроліз триває при високій напрузі, іони заліза та хрому накопичуються в електроліті. Встановлено, що при електросинтезі водню з електродними парами Ti (BT6) – Zn та Ni – Zn відбувається зниження напруги на електролізері на 1-1,2 В, що дозволяє заощаджувати електроенергію.

The behavior of electrode materials at the hydrogen electrosynthesis with 3% ammonium chloride solution was investigated. Overvoltage of hydrogen evolution on the vanadium containing electrodes is less in comparison with nickel electrodes. The ability of using titan VT6 alloy as a cathode material in practical electrolysis in a wide range of current densities and pH values has been proved. This alloy has a high chemical resistance. The 12H1МF steel using as the anode material is not effectively. Electrolysis occurs at high voltage and iron and chromium ions accumulate in the electrolyte. The decrease of voltage at the electrolyzer for 1-1,2 V at the hydrogen electro synthesis with electrode pairs Ti (VT6) – Zn and Ni – Zn has been established. Electricity saving is allowed by this fact. Voltage drop is caused by the effect of anodic depolarization reaction. In a solution of ammonium chloride on the zinc electrode, instead of the oxygen evolution reaction, the zinc dissolution is occurred.
Study of the influence of electrode material nature on the parameters of the hydrogen electrosynthesis
Keywords: електродні матеріали; водень; перенапруга; електросинтез; деполяризація; електродна пара; electrode materials; hydrogen; overvoltage; electrosynthesis; electrode pair